The Effectiveness Of QirÄatul Kutub Learning In Improving Reading Skills Of The Yellow Book At Madrasah Aliyah Muallimin Al Washliyah Univa Medan - Saiful Akhyar Lubis; Achyar Zein; Khairul Anwar; M Fajri Syahroni Siregar (At-Tarbiyat, 2021)
This study aims to describe the effectiveness of QirÄatul Kutub's learning in improving the understanding of the Yellow Book at Madrasah Aliyah Muallimin Univa Medan. This type of research is qualitative research. The research data collection technique was conducted by interview, observation, and documentation. The results of the study are that 1) Qiraatul Kutub learning in improving the understanding of the Yellow Book at Madrasah Aliyah Muallimin is less effective, due to the variety of students who enter madrasas so that it becomes an obstacle when teachers teach the subjects taught to students, lack of time and in terms of comfort. 2) The factors that influence the effectiveness of Qiraatul Kutub learning in improving the understanding of the Yellow Book at Madrasah Aliyah Muallimin UNIVA Medan are human resources, facilities, and infrastructure and methods. 3) The solution taken to overcome the factors that affect the effectiveness of Qiraatul Kutub learning in improving the understanding of the Yellow Book at Madrasah Aliyah Muallimin UNIVA Medan is to formulate a simple book for students before they enter a higher book, form a particular group for teachers- teacher of the turrets book.